Special education international perspectives biopsychosocial, cultural, and disability aspects - Rotatori, Anthony F. (Advances in special education ;, 2014)
The volume will be divided into four parts. Part 1 will present an overview on disability that focuses on two major themes, namely, the biopsychosocial approaches to disability and cultural views of disability. Part 2 will examine five major areas of high incidence exceptionalities: cognitive impairment, learning disabilities and attention deficit hyperactivity, autism spectrum disorders, behavioural/emotional disorders and speech and language disorders.